Atomistic study of stability and new phase transitions of zinc selenide using FP-LMTO-PLW method - Hamza, REKAB DJABRI; Salah, DAOUD; Youcef, GUERMIT; Nabil, BELOUFA; Souad, LOUHIBI FASLA (International Journal of Physical Research, 2022)
By full potential linear muffin-tin orbitals (FP-LMTO-PLW) method, we have studied the phase transitions of ZnSe under high pressures. The local density approximation (LDA) was used for the exchange and correlation energy. The most important result is the prediction of the possibility of four phase transitions from the cubic zincblende (ZnS-B3) to the B81 (NiAs) structure at 8.00 GPa, the second from B3 to the B32 (NaTi) and Bh (WC) structures at above 45 GPa for each one of them, and from B3 to B2 (CsCl) phase at around 31GPa. The first one (ZnS–NiAs) occurring at a lower pressure than the well knownZnS to NaCl transition (found here to be 11.5 GPa).